Bureaucracy and development administration - Ahmad, Furqan (New Delhi : Manak Publications, 1995)
Study based on some districts of Uttar Pradesh.
Includes bibliographies and index.
Keywords: Civil service -- India -- Uttar Pradesh; Public administration -- India